Investigate the influence of the penetration level of PV distributed generation and energy storage integration on the medium voltage distribution network - Alqadi, Haitham (جامعة بوليتكنك فلسطين - طاقة)
Electrical power system is centralized energy frames, power flows from generation plant to distribution network through transmission lines of the grid, which means that the conventional system has unidirectional power flow. The increasing of electrical energy consumption and the immediate need of electricity today leads to enhance and develop the electrical power system . Using of renewable energy system, especially solar energy is one of the solutions to produce sustainable and environmentally friendly electrical energy systems. This study supports the photovoltaic (PV) system as a renewable source , but the intermittency of the solar energy and variation of weather conditions, besides of high impact of the high penetration of PV systems are stand as a main drawback of the grid connected PV system……..
Keywords: influence of the penetration level of PV distributed generation and energy storage integration on the medium voltage distribution network